Prescribing Patterns of Direct-Acting Oral Anticoagulants in Patients With Atrial Fibrillation and Chronic Kidney Disease: A Retrospective Cohort Analysis - Jorge L. Reyes MD; Charles A. Herzog MD; Heng Yan MS; Nicholas S. Roetker PhD; James B. Wetmore MD, MS (SAGE Publishing, 2022)
Background: The association of patient and prescriber characteristics with use of warfarin versus direct-acting oral anticoagulants (DOACs) in patients with atrial fibrillation (AF) and chronic kidney disease (CKD) is not well studied. Methods: The 20% Centers for Medicare & Medicaid Services Parts A, B, and D claims data from 2010 to 2017 were used to identify patients with stage 3, 4, or 5 CKD and AF who received a DOAC (apixaban, dabigatran, rivaroxaban) or warfarin. Prescribers were categorized as cardiologists, primary care providers (PCPs), and others. Using logistic regression, we estimated odds ratios (ORs) for the association of baseline characteristics and prescriber specialty with first use of a DOAC, relative to warfarin. Results: We identified 22,739 individuals with CKD who were newly initiated on oral anticoagulation for AF. New DOAC prescriptions increased from 490 in 2011 to 3261 in 2017, and displaced warfarin over time (1849, 2011; 945, 2017). By Q4 of 2014, cardiologists prescribed DOACs as initial treatment more frequently than warfarin, but non-cardiologists did not do so until 2015. As of 2017, apixaban was the most widely prescribed anticoagulant, comprising 56% and 50% of prescriptions by cardiologists and non-cardiologists, respectively. PCPs (OR 0.54, 0.51-0.58) and other providers (OR 0.55, 0.51-0.59) were less likely than cardiologists to prescribe DOACs. Conclusions: DOAC prescriptions, particularly apixaban, increased over time and gradually displaced warfarin. The total number of patients with AF and CKD receiving anticoagulation increased over time. Cardiologists increased DOAC prescriptions more rapidly than non-cardiologists.